90 DAYS: An investigation of a short entertainment-education film to improve HIV status disclosure among black women living with HIV in Miami-Dade County. (February 2021) - Simmons, Jazmyne V.; Carcioppolo, Nick; Peng, Wei; Huang, Qian; Seelig, Michelle; Katz, Rachel; Potter, JoNell
Abstract: Within Miami-Dade County, Black women experience disproportionate rates of HIV incidence and prevalence. Status disclosure to sexual partners is central to mitigating the HIV epidemic and ensuring a healthier lifestyle for those living with the virus. The disclosure processes model (DPM) posits that barriers such as stigma and negative outcome expectations often facilitate disclosure avoidance. Therefore, this study investigated the utility and acceptability of an entertainment-education (EE) short film, 90 DAYS, for disclosure among Black women living with HIV in Miami-Dade County. Employing photo-elicitation (Harper, 2002), focus groups were conducted with 48 participants. After screening the 90 DAYS film about stigma and disclosure, participants were asked semi-structured questions based upon extant EE and DPM literature. Via inductive and deductive processes, five themes were derived from the data. Participants found the 90 DAYS film to be an empowering counter-narrative that could be used to overcome multiple disclosure-related factors. They felt it provided a social script for how to disclose to their sexual partners. A novel finding of this investigation was that respondents asserted the film could facilitate safer disclosure events. Additional themes included the film being a resource of hope for young and newly diagnosed women; and an educational tool for the community. Altogether, findings lend promise to the use of EE for addressing disclosure avoidance among Black women living with HIV. Highlights: Entertainment-education is an acceptable tool for addressing serostatus disclosure. Participants saw the 90 DAYS film as useful to assess safety of a disclosure event. Participants perceived the film can influence key disclosure communication skills. Entertainment-education may be useful for addressing disclosure antecedents.